Performance Direction towards Performance Achievement: Case on Local Islamic Banks in Malaysia - Shamsudin, Norazidah; Mohammed, Mustafa Omar (JOEBM, 2015)
Performance of a company is important for identifying its survival ranking and for its future direction, improvement and development strategy. Bank performance has conventionally been measured using financial ratios and several quantitative indicators, which appraise its financial strength. The same yardstick is being used by Islamic banks to measure their performance. This practice gives rise to the question whether Islamic banks appear to be focusing on Maqasid al-Shari'ah in their achievements or they share the same primary intention of conventional commercial banks, which strive for maximizing shareholders’ wealth. Scholars have raised concern that Islamic banks seem to be replicating the conventional banking system and this is creating a widening gap between the theory and practice of Islamic banking. Hence, this study has used a sample of 18 banks in Malaysia to critically review the organization’s vision and mission statements based on Maqasid al-Shari'ah by embracing content analysis and behavioral science operationalization method. The results show that the majority of Islamic banks have focused on the concept of establishing justice with emphasis on the elimination of negative elements that breed injustice, whereas conventional banks have put emphasis on profitability of the bank, categorized under the maslahah concept. Since there is different focus between the conventional and Islamic banks, there is a need for Islamic banks to evaluate their performance within their own framework and using their own criteria.